The effect of polymer blending or coating on the preparation of alginate microspheres containing a hydrophilic β-lactam antibiotic - Chun, K.H.; Kwon, I.C.; Kim, Y.H.; Sohn, Y.T.; Jeong, S.Y. (Proceedings of the Controlled Release Society, 1996)
[No abstract available]